2015
DOI: 10.1016/j.yjmcc.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

High fat, high sucrose diet causes cardiac mitochondrial dysfunction due in part to oxidative post-translational modification of mitochondrial complex II

Abstract: Background Diet-induced obesity leads to metabolic heart disease (MHD) characterized by increased oxidative stress that may cause oxidative post-translational modifications (OPTM) of cardiac mitochondrial proteins. The functional consequences of OPTM of cardiac mitochondrial proteins in MHD are unknown. Our objective was to determine whether cardiac mitochondrial dysfunction in MHD due to diet-induced obesity is associated with cysteine OPTM. Methods and results Male C57Bl/6J mice were fed either a high-fat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 31 publications
11
109
2
1
Order By: Relevance
“…Complex III represents a confluence point for reducing equivalents from various dehydrogenases; it can catalyze the transfer of electrons from hydroxyquinones. This finding was in contrast to the striking observation of mitochondrial dysfunction in the liver from the high-fat induced mice without cathechins once there was a significant increase in activity of the II-III complexes in hyperlipidic group [13,61] (Figure 4). …”
Section: Accepted Manuscriptcontrasting
confidence: 63%
See 2 more Smart Citations
“…Complex III represents a confluence point for reducing equivalents from various dehydrogenases; it can catalyze the transfer of electrons from hydroxyquinones. This finding was in contrast to the striking observation of mitochondrial dysfunction in the liver from the high-fat induced mice without cathechins once there was a significant increase in activity of the II-III complexes in hyperlipidic group [13,61] (Figure 4). …”
Section: Accepted Manuscriptcontrasting
confidence: 63%
“…Several studies in humans [36][37][38][39] and rodents [8,13,18,40,41] presented strong evidence that HFD, particularly rich in saturated fatty acids, promoted the development of three pathological features associated with the metabolic syndrome: dyslipidemia, insulin resistance/glucose intolerance, and increased visceral adiposity [42]. Our experimental model of diet to induce obesity proved to be effective in simulating obesity with treatment of 16 weeks.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, bioinformatics classification and network analysis were carried out to investigate functional connections between identified proteins and key fatty acid metabolic targets (AMPK, ACC, and FAS). It has been demonstrated that HFD intake leads to dietinduced obesity along with many disease risk factors in association with increased post-translational modification (PTM), production of advanced glycation end products, and apoptosis [46,47]. Our proteomic data confirmed five proteins having the same molecular weight but different pIs, indicating the proteins underwent PTM.…”
Section: Discussionsupporting
confidence: 57%
“…In addition to these state of the art review articles this special issue also contains several original research articles [27][28][29][30]. Taken together this special issue provides up to date reviews as well as original research articles on some of the hottest topics in mitochondrial biology.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%